Interpersonal Communication Model and Learning Readiness Among Santri in Achieving The Success of Study at Higher-Educational Institutions - Sholeh, Ahmad; Yaqien, Nurul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine to what extent the education system of Islamic boarding schools (known as Pondok Pesantren) is related to the model of interpersonal communication and pesantren students (known as santri) readiness to learn can contribute to their success while taking the level in higher education. The authors used the quantitative method as the research approach. This research was conducted at the Pondok Pesantren